1983
DOI: 10.1002/iroh.19830680106
|View full text |Cite
|
Sign up to set email alerts
|

Oxygen Consumption and Dissolved Inorganic Nutrient Production in Marine Coastal and Shelf Sediments of the Middle Atlantic Bight

Abstract: The benthic oxygen demand and inorganic nutrient release have been investigated in the coastal zone of the Mid-Atlantic Bight of the United States using in situ and ship-board incubations t,o estimate fluxes across the sediment-water interface. Oxygen demand ranged from ca. 70 nil m-2 hr-1 nearshore in warm (25 "C) muddy sediments to ca. 4 ml m-? hr-1 in cold (6 "C), coarse-grained sediments offshore. Ammoniumionflux was out of the sediments in all but 4 of 29 incubations, while nitrate was often found to be u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
16
0

Year Published

1983
1983
2013
2013

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 52 publications
(22 citation statements)
references
References 57 publications
5
16
0
Order By: Relevance
“…Kelderman 1984). Our values for ammonia release in the dark (0.5 mm01 NH4 m-' d-' in aquaria without added nutrients) lie well within the range of those reported by Boynton & Kemp (1985) and Nowicki & Nixon (1985), but are somewhat lower than rates reported by Florek & Rowe (1983). Boynton & Kemp found that in Chesapeake Bay the ammonia release was highest in summer, max.…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…Kelderman 1984). Our values for ammonia release in the dark (0.5 mm01 NH4 m-' d-' in aquaria without added nutrients) lie well within the range of those reported by Boynton & Kemp (1985) and Nowicki & Nixon (1985), but are somewhat lower than rates reported by Florek & Rowe (1983). Boynton & Kemp found that in Chesapeake Bay the ammonia release was highest in summer, max.…”
Section: Discussionsupporting
confidence: 85%
“…While nitrate fluxes are often directed towards the sediment because of denitrification, at least when there are high nitrate concentrations in bottom-near waters (as in our experiment), there is usually a net outflow of ammonia from sediments (Florek & Rowe 1983, Boynton & Kemp 1985, Nowicki & Nixon 1985.…”
Section: Discussionmentioning
confidence: 68%
“…The enhancement of these two components may result in the lower permeation of oxygen, increased microbial oxygen uptake/demand and a subsequent build up of toxic by-products (e.g. ammonia, dissolved sulphide) (Florek & Rowe, 1983;Santschi et al, 1990;Fenchel et al, 1998). This can lead to impoverished benthic communities dominated by a few opportunistic species, as supported by the low MI values and the dominance of rstrategist genera at site B.…”
Section: Discussionmentioning
confidence: 99%
“…The regeneration of nutrients and fluxes of gases at the sediment-water interface has often been compared to the typical elemental composition of organic matter mainly originating from phytoplankton in the sea as described by Redfield (1934) (Nixon et al 1976, Florek & Rowe 1983. However, detritus derived from macrophytes may have a different elemental composition to planktonic detritus, which may influence the regeneration processes.…”
Section: Introductionmentioning
confidence: 99%